Pattern study of union of two heads of biceps and its clinical significance - Rohilla, Jyoti; Rohilla, Aarti; Singh, Kamal; Rathee, Suresh Kanta (International Journal of Research in Medical Sciences, 2017)
Background: Biceps brachii derives its name from its two proximally attached parts or ‘heads’ that is known as long head and short head. Two tendons form elongated bellies that though closely applied get fused within 7cm or so above the elbow joint. These variations should be kept in mind during surgical and diagnostic procedures done by clinicians. Methods: A total of 18 cadavers were dissected for two successive years during undergraduate and were observed for different patterns of fusion of two heads of biceps brachii. Results: The present study showed that frequency of fusion of heads of biceps brachii in its upper one-third part was observed less commonly while it was frequently observed in its middle one-third part. Conclusions: Variation in union of heads might be significant in causing compression of neurovascular structures because of their close relationship to the brachial artery and median nerve.